Effects of estrogen on gene expression in chick oviduct: nuclear receptor levels and initiation of transcription. - Tsai, S Y (1975)
Estrogen (diethylstilbesterol) was administered in vivo to chicks for various time periods. Chromatin was then prepared from oviduct nuclei and assayed for its capacity to support initiation of RNA chain synthesis in vitro in the presence of saturating levels of Escherichia coli RNA polymerase (RNA nucleotidyltransferase; nucleosidetriphosphate:RNA nucleotidyltransferase; EC 2.7.7.6). These same nuclei were also assayed by a [3H]estradiol exchange assay for their endogenous receptor content. The number of available initiation sites for RNA synthesis on chromatin was shown to correlate with the endogenous levels of nuclear estrogen receptor. A decrease in the nuclear concentration of estrogen receptor molecules and the concentration of initiation sites for RNA synthesis occurred during withdrawal of estrogen from previously stimulated chicks. Both parameters declined with a similar half-life. When estrogen was readministered to withdrawn chicks, the number of initiation sites increased 2-fold as early as 30 min and approached a maximal level (3-fold) by 1 hr. During the same period of restimulation with estrogen, the number of estrogen receptor molecules bound to nuclei increased to a maximum at 20 min and then declined at 1 hr to a steady-state level 2-fold higher than the withdrawn chicks. Simultaneous measurements of RNA chain length and RNA chain propagation rate demonstrated that parameters remained relatively constant throughout estrogen withdrawal as well as secondary stimulation. The temporal correlation between changes in the levels of nuclear-bound estrogen receptor and the number of RNA chain initiation sites on chromatin prepared from these same nuclei strongly suggested that the hormone receptor complexes act on chromatin to mediate these changes in genetic transcriptional activity.